A study on reintegration of street children in Burundi: experienced violence and maltreatment are associated with mental health impairments and impeded educational progress - Crombach, Anselm; Bambonyé, Manassé; Elbert, Thomas (Frontiers in Psychology, 2014)
Street children are exposed to violence, and subsist in poor and generally precarious conditions. In conflict regions, institutional care facilities are often the only well established way to care for vulnerable children. Providing access to school education is considered to be key to allow successful integration into society. However, adverse effects of psychological disorders may pose another serious obstacle. In semi-structured interviews in a sample of 112 Burundian male youths (mean age = 15.9 years), we assessed exposure to traumatic stressors, regularly and recently occurring violence as well as prevalence of posttraumatic stress disorder (PTSD), depression, substance dependence, suicidal risk, and progress in school. Former street children (n = 32) and other vulnerable children (n = 50) in a residential center were compared to children living in the streets (n = 15) or with families (n = 15). While the children living in the center were less regularly exposed to violence and reported less substance dependence than street children, PTSD symptoms were common among the former street children. Furthermore, we provided empirical evidence that for the children living in the center, recently experienced violence – mostly minor physical conflicts, psychological violence and neglect – was associated with increased PTSD symptomatology and impeded progress in school. In a population of children who experienced many traumatic incidences and a lot of violence, even minor violent events may trigger and reinforce PTSD symptoms. Hence controlling exposure to violence and addressing mental ill-health in vulnerable children is mandatory for reintegration.